2015
DOI: 10.1021/acs.jafc.5b03132
|View full text |Cite
|
Sign up to set email alerts
|

Production, Purification, and in Vitro Evaluation of the Prebiotic Potential of Arabinoxylooligosaccharides from Brewer’s Spent Grain

Abstract: Brewer's spent grain (BSG) samples were subjected to a two-step aqueous processing (starch extraction and autohydrolysis) in order to assess their potential as a raw material for obtaining a mixture of arabinoxylooligosaccharides (AXOS) suitable to be use as prebiotics for elderly. After hydrothermal treatment, the liquors were refined by a sequence of purification and conditioning steps including membrane filtration, enzymatic hydrolysis, and ion exchange. The presence of both substituted (degree of polimeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 50 publications
(110 reference statements)
5
48
1
Order By: Relevance
“…As an example, bifidobacteria produce short chain fatty acids (SCFA) through fermentation of dietary fibres. Recently, Gomez et al (42) demonstrated that the in vitro prebiotic potential of arabinoxylooligosaccharides from BSG was higher than that of fructooligosaccharides. The breakdown of AX yields xylooligosaccharides (XOS) with varying degrees of polymerisation, which are known prebiotics (39) and are possibly the reason for the prebiotic activity of AX.…”
Section: Health Benefits Of Bsg and Its Constituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, bifidobacteria produce short chain fatty acids (SCFA) through fermentation of dietary fibres. Recently, Gomez et al (42) demonstrated that the in vitro prebiotic potential of arabinoxylooligosaccharides from BSG was higher than that of fructooligosaccharides. The breakdown of AX yields xylooligosaccharides (XOS) with varying degrees of polymerisation, which are known prebiotics (39) and are possibly the reason for the prebiotic activity of AX.…”
Section: Health Benefits Of Bsg and Its Constituentsmentioning
confidence: 99%
“…Hughes et al (41) investigated the prebiotic potential of different molecular weight fractions of AX, finding that a low molecular weight fraction (66 kDa) was most selective for 'health promoting' bacterial groups and an elevated production of SCFA, particularly butyrate. Recently, Gomez et al (42) demonstrated that the in vitro prebiotic potential of arabinoxylooligosaccharides from BSG was higher than that of fructooligosaccharides. Similar results were observed by Reis et al (43) with AX fractions isolated using ultrasound assisted extraction.…”
Section: Health Benefits Of Bsg and Its Constituentsmentioning
confidence: 99%
“…Some researchers have assessed the content of this OS in agro‐industrial by‐products; for example, barley flour contains 5.02% arabinoxylan and brewer's spent grain 14.75% arabinoxylan (Sajib et al, ). Also, Gomez, Miguez, Veiga, Parajo, and Alonso () reported that brewer's spent grain is composed of glucan (24.91%), xylan (13.94%), arabinan (6.68%), and acid insoluble residue (22.82%). Nowadays, AXOS are considered as prospective functional ingredients due to their prebiotic effect (Yamada et al, ).…”
Section: Oligosaccharides As Prebiotic Compoundsmentioning
confidence: 99%
“…The same authors evaluated the clostridia population and found the same number observed as the control, which suggests that the growth of this population may be due to the components of the basal medium. Besides, this AXOS were not selectively used by bacteroides (Gómez et al, ). In another study, the fermentation of AXOS from wheat bran with fecal inoculum demonstrated an increased bifidobacteria population in comparison with FOs (Gullón, Gullon, Tavaria et al, ).…”
Section: Oligosaccharides As Prebiotic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation